Two new species of Nolina (Nolinoideae: Asparagaceae) endemic to Western Mexico - Ruiz-Sanchez, Eduardo; Carrillo-Reyes, Pablo; Hernández-Sandoval, Luis Gerardo; Specht, Chelsea D. (Phytotaxa, 2019)
Nolina in Mexico is represented by 26 described species, 18 of them are endemic. Previous molecular and ecological studies indicated that populations of Nolina parviflora from Jalisco and Zacatecas may be genetically and ecologically distinct from the described N. parviflora and therefore merit delimitation as a separate species. A detailed morphological study of samples from Jalisco and Zacatecas and a review of existing herbarium collections confirmed the existence of two new Nolina species, which are here described and illustrated as Nolina caxcana and Nolina rodriguezii. Both species are endemic to Mexico.